WUJUD DAN FAKTOR PENYEBAB KESALAHAN PEMAKAIAN BAHASA JAWA KRAMA DAN CARA MEMPRESERVASINYA - Pranowo Pranowo; Benedictus Bherman Dwijatmoko; Danang Satria Nugraha (Widyaparwa, 2021)
This study discusses "The Form and Factors Causing Errors in Using the Javanese Language of Manners and Cras for Preserving It". This study uses the theory of language relativity to analyze errors in the use of Javanese. Sources of data are students who are in the working environment of researchers. The data is in the form of Javanese speech manners. Data collection techniques are in the form of questionnaires and structured interviews by means of fishing techniques via e-mail or WhatsApp (WA). Data analysis techniques consist of data identification, data classification, and data interpretation. The results of the study are (1) the form of errors in the use of errors in the use of Javanese manners (various types of words and affixes). The causal factor is because (a) they have not been able to distinguish the vocabulary of Javanese krama from Indonesian, (b) have not been able to distinguish the use of Javanese krama for oneself and for parents or other respected people, (c) the Javanese language mastered is limited to "krama ndesa", (d) adjectives that do not have concrete references are a problem in itself, and (e) many of the Javanese krama affixes used are incomplete, (2) the preservation of the Javanese krama language needs to be carried out so that the Javanese krama language remains sustainable. However, there are still some obstacles faced, namely (a) many parents no longer use BJ krama, (b) the younger generation speaks accustomed to using Javanese ngoko or Indonesian, (c) some Javanese language teachers are not from their fields, (e) many BJ teachers are not creative enough, and (f) the younger generation of Javanese who are not good enough get less motivation from their environment.Penelitian ini membahas “Wujud dan Faktor Penyebab Kesalahan Pemakaian Bahasa Jawa krama dan Cara Mempreservasinya”. Penelitian menggunakan teori relativitas bahasa untuk menganalisis kesalahan pemakaian bahasa Jawa. Sumber data adalah  para mahasiswa yang berada di lingkungan kerja peneliti. Data berupa tuturan bahasa Jawa krama. Teknik pengumpulan data berupa angket dan wawancara terstruktur dengan cara teknik pancing lewat e-mail atau WhatsApp (WA). Teknik analisis data terdiri atas identifikasi data, klasifikasi data, dan interpretasi data. Hasil penelitian berupa dua temuan. Pertama, wujud kesalahan pemakaian kesalahan pemakaian bahasa Jawa krama  pada berbagai jenis kata dan imbuhan). Faktor peyebabnya adalah karena (a) belum mampu membedakan kosakata bahasa Jawa krama dengan bahasa Indonesia, (b) belum dapat membedakan per-untukan bahasa Jawa krama untuk diri sendiri dan untuk orang tua atau orang lain yang dihormati, (c) bahasa Jawa yang dikuasai terbatas pada “krama ndesa”, (d) kata sifat yang tidak memiliki acuan konkret menjadi kesulitan tersendiri, dan (e) banyak imbuhan bahasa Jawa krama yang dipakai tidak lengkap. Kedua, preservasi bahasa Jawa krama yang perlu terus dilakukan agar bahasa Jawa krama tetap lestari. Namun masih terdapat beberapa kendala yang dihadapi, yaitu (a) banyak orang tua tidak lagi menggunakan BJ krama, (b) generasi muda bertutur terbiasa menggunakan bahasa Jawa ngoko atau bahasa Indonesia, (c) sebagian guru bahasa Jawa bukan dari bidangnya, (e)  banyak guru BJ yang kurang kreatif, dan (f) bahasa Jawa generasi muda yang belum baik kurang mendapat motivasi dari lingkungannya.